Determination of some heavy metals in Mastacembelus mastacembelus (Banks & Solander, 1794) in terms of public health - Eroğlu, M.; Düşükcan, M.; Canpolat, í–.; í‡alta, M.; Åžen, D. (Cellular and Molecular Biology, 2017)
In this study, the accumulation of some heavy metals in spiny eel (Mastacembelus mastacembelus Banks and Solander, 1794) living in Karakaya Dam Lake was determined and human health risk of this fish when consumed as food was examined. For this purpose, the amounts of copper (Cu), chromium (Cr), cadmium(Cd), iron (Fe), zinc (Zn) in water samples and in the muscle tissues of the fishes were determined. The amounts of heavy metals showed differences in the muscle tissues of Mastacembelus mastacembelus according to weight, length, sex and age groups of fish. In conclusion the amounts of heavy metals in the flesh of spiny eels were found lower than that recommended by EPA, WHO, FAO and TFC.